# |
ODE |
Mathematica |
Maple |
\[
{}y+x +x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6 x -2 y+1+\left (2 y-2 x -3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right ) \cos \left (y\right )^{2}-\cos \left (x \right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{2}-x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 \left (1-y^{2}\right ) x y+\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{\frac {y}{x}}+y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+3 y^{3}-\left (x^{3}+2 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y+y^{3}-x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y \cos \left (\frac {y}{x}\right )-x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x +3 y+1+\left (x +y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x -y+2+\left (x +y+3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y-\left (4 x +2 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 x y^{2}-x^{2} y^{3}+2 x^{2} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y+3 x y^{2}+\left (x +2 x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+x y^{2}+\left (x -x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\left (1+x \right ) y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 y}{1+x} = \left (1+x \right )^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+x \right ) y^{\prime }+4 x^{2} y = 2
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+\left (1-2 x \right ) y = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-2 \left (1+x \right ) y = y^{{5}/{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x y^{2} = x
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right ) y^{\prime }+\sin \left (x \right ) \cos \left (y\right ) = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime }+3 y+{\mathrm e}^{x} x^{4} y^{5} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {1+y}{1+x} = \sqrt {1+y}
\] |
✓ |
✓ |
|
\[
{}x^{4} y \left (3 y+2 x y^{\prime }\right )+x^{2} \left (4 y+3 x y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (3 y-6 x y^{\prime }\right )-x \left (y-2 x y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y-y^{2}-\left (2 x^{4}+x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime }-y}{\sqrt {x^{2}-y^{2}}} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x +y-\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+6 x y+3 y^{2}+\left (2 x^{2}+3 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +\left (x^{2}+y^{2}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4}+2 y+\left (x y^{3}+2 y^{4}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y-y^{4}+\left (x y^{3}-x^{4}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x^{2}+2 m x y+\left (m y^{2}-m \,x^{2}-2 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y+2 x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime }+y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-a y+b y^{2} = c \,x^{2 a}
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1-y^{2}}+y \sqrt {-x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {1-y^{2}}+\sqrt {-x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x^{2} y = x^{5}
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right )^{2} y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y+x^{4} y^{4} {\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y+\left (1-y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}-y^{2}}
\] |
✓ |
✓ |
|
\[
{}\sin \left (\frac {y}{x}\right ) x -y \cos \left (\frac {y}{x}\right )+x \cos \left (\frac {y}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y+5+\left (2 x -y+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\left (-x^{2}+1\right )^{{3}/{2}}} = \frac {x +\sqrt {-x^{2}+1}}{\left (-x^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-x y = a x y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{2} \left (3 y+x y^{\prime }\right )+x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+y = \arctan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}5 x y-3 y^{3}+\left (3 x^{2}-7 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \frac {\sin \left (2 x \right )}{2}
\] |
✓ |
✓ |
|
\[
{}x y^{2}+y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y-\left (1+y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y+\left (x^{3}+y^{2} x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) \left (x +y y^{\prime }\right ) = \left (x^{2}+y^{2}+x \right ) \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}2 x +3 y-1+\left (2 x +3 y-5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}-2 x^{2} y+\left (2 x y^{2}-x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{2} x^{3}-y+\left (2 x^{2} y^{3}-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) \left (x +y y^{\prime }\right )+\sqrt {1+x^{2}+y^{2}}\, \left (-x y^{\prime }+y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{\frac {y}{x}}+{\mathrm e}^{\frac {x}{y}} \left (1-\frac {x}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y-y^{2} \ln \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{4} x^{3}+x^{2} y^{3}+x y^{2}+y+\left (y^{3} x^{4}-y^{2} x^{3}-x^{3} y+x \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\left (2 \sqrt {x y}-x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (2 x y^{\prime }-y\right )^{2} = 8 x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (y^{2}+2 x \right ) {y^{\prime }}^{2}+\left (x^{2}-y^{2}+2 x y^{2}\right ) y^{\prime }-y^{2} \left (x^{2}-y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-y+\ln \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}4 x {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y = -x y^{\prime }+x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x +y^{\prime } y \left (2 {y^{\prime }}^{2}+3\right ) = 0
\] |
✗ |
✓ |
|
\[
{}a^{2} y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }-x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 x y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}4 \,{\mathrm e}^{2 y} {y^{\prime }}^{2}+2 \,{\mathrm e}^{2 x} y^{\prime }-{\mathrm e}^{2 x} = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{2 y} {y^{\prime }}^{3}+\left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x} = 0
\] |
✗ |
✓ |
|
\[
{}x y^{2} {y^{\prime }}^{2}-y^{3} y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) \left (y^{\prime }+1\right )^{2}-2 \left (x +y\right ) \left (y^{\prime }+1\right ) \left (x +y y^{\prime }\right )+\left (x +y y^{\prime }\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}a^{2} y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -y^{\prime }-y\right )^{2} = x^{2} \left (2 x y-x^{2} y^{\prime }\right )
\] |
✗ |
✗ |
|